The model of psychopathogenesis of nonpsychotic mental disorders in persons undergoing the programs of synthetic opioids substitution therapy - Chugunov, V. V.; Gorodokin, A. D.; Чугунов, Вадим Віталійович; Городокін, Антон Дмитрович; Чугунов, В. В.; Городокин, А. Д. (My University, 2018)
In order to identify the structural and dynamic characteristics of comorbid non-psychotic psychopathological symptoms in patients on the synthetic opioid substitution therapy program, 100 patients of the narcological dispensary were examined with the help of the Simptom Check List – 90 – Revised. The study used the inclusion and exclusion criteria that are identical to the criteria for participation in the substitution therapy program. The results were distributed to 3 levels, which correspond to the degree of clinical significance of the symptoms: - minimal (discomfort for this reason occurs rarely or does not occur at all, it has a low intensity) - the range of results obtained is from 0 to 0.50; - subclinical (the presence of not frequent, moderately intense discomfort for this reason) - the range of values is from 0.51 to 1.50; - clinical (frequent or persistent high intensity discomfort for this reason) - range of values greater than 1.51. The study found that non-psychotic mental disorders among this group of patients have three stages of development. All groups of symptoms are considered in the context of the three main classes of disorders (patho-affective — anxiety and depression symptoms; pseudo-neurotic — obsessivecompulsive phenomena; psycho-vegetative symptoms and self-perception disorders; and psychoorganic — associative disorders, paranoia and hostility) and two groups of intermediate symptoms (phobic — intermediate between pathogenic and pseudoneurotic and psychotic - intermediate between psychoorganic and pseudoneurotic). Also, according to the results of the assessment of the correlation dynamics of symptom groups, a model of psycho-pathogenesis of non-psychotic mental disorders in people who are on the program of drug addiction substitution therapy was constructed. З метою виявлення структурно-динамічної характеристики коморбидної непсихо- тичної психопатологічної симптоматики у хворих, які перебувають на програмі заміс- ної терапії синтетичними опіоїдами, за допомогою симптоматичного опитувальника (Simptom Check List-90-Revised) було обстежено 100 пацієнтів наркологічного диспан- серу. У дослідженні використані критерії включення і виключення, ідентичні критеріям участі в програмі замісної терапії. Отримані результати були розподілені на 3 рівня, які відповідають ступеню клінічної значущості симптомів: - мінімальний (дискомфорт з цієї причини відбувається рідко або взагалі не виникає, він має низьку інтенсивність) - діа- пазон отриманих результатів від 0 до 0,50; - субклінічний (наявність не частого, помір- но інтенсивного дискомфорту через це) - діапазон значень від 0,51 до 1,50; - клінічний (частий або постійний високої інтенсивності дискомфорт з цієї причини) - діапазон зна- чень більше 1,51. В результаті дослідження було виявлено, що непсихотичні психічні розлади серед даного контингенту хворих мають три етапи розвитку; всі групи сим- птомів розглядаються в контексті трьох основних класів розладів (патоафектівні - сим- птоми тривожністі і депресії, псевдоневротичні - обсесивно-компульсивні явища, психовегетативні симптоми і порушення самосприйняття і психоорганічні - асоціативні порушення, паранояльність і ворожість) та двох груп проміжних симптомів (фобічні - проміжні між патогенними і псевдоневротичними і психотичні - проміжні між психоорганічними і псевдоневротичними). Так само за результатами оцінки кореляційної динаміки груп симптомів була побудована модель психопатогенезу непсихотичних психічних розладів у осіб, які перебувають на програмі замісної терапії наркоманії. С целью выявления структурно-динамической характеристики коморбидной непсихотической психопатологической симптоматики у больных, находящихся на программе заместительной терапии синтетическими опиоидами, при помощи Симптоматического опросника (Simptom Check List–90–Revised) было обследовано 100 пациентов наркологического диспансера. В исследовании использованы критерии включения и исключения, идентичные критериям участия в программе заместительной терапии.Полученные результаты были распределены на 3 уровня, которые соответствуют степени клинической значимости симптомов: - минимальный (дискомфорт по этой причине происходит редко или вообще не возникает, он имеет низкую интенсивность) – диапазон полученных результатов от 0 до 0,50; - субклинический (наличие не частого, умеренно интенсивного дискомфорта по данной причине) – диапазон значений от 0,51 до 1,50; - клинический (частый или постоянный высокой интенсивности дискомфорт по этой причине) – диапазон значений болеее 1,51. В результате исследования было обнаружено, что непсихотические психические расстройства среди данного контингента больных имеют три этапа развития; все группы симптомов рассматриваются в контексте трех основных классов расстройств (патоаффективные – симтомы тревожности и депрессии, псевдоневротические – обсессивно-компульсивные явления, психовегетативные симптомы и нарушения самовосприятия и психоорганические – ассоциативные нарушения, паранояльность и враждебность) и двух групп промежуточных симптомов (фобические – промежуточные между патогенными и псевдоневротическими и психотические – промежуточные между психоорганическими и псевдоневротическими). Так же по результатам оценки корреляционной динамики групп симптомов была построена модель психопатогенеза непсихотических психических расстройств у лиц, находящихся на программе заместительной терапии наркомании.
Модель психопатогенезу непсихотичних психічних розладів у осіб, які проходять програму синтетич- ної опіоідної замісної терапії.
Модель психопатогенеза непсихотических психических расстройств у лиц, проходящих программу синтетической опиоидной заместительной терапии.
Keywords: replacement therapy; methadone; neurotic disorders; narcology; замісна терапія; метадон; невротичні розлади; наркологія; заместительная терапия; метадон; невротические расстройства; наркология